2018
DOI: 10.3389/fped.2018.00139
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus mongholicus (Fisch.) Bge Improves Peripheral Treg Cell Immunity Imbalance in the Children With Viral Myocarditis by Reducing the Levels of miR-146b and miR-155

Abstract: Viral myocarditis (VMC) is a common cardiac disease, however, there still lacks an effective therapeutic strategy for VMC. Astragalus mongholicus (Fisch.) Bge (AB), a Chinese herb with some functional metabolites, may have some pharmacological effects on VMC. AB ingredients were measured by a full-scan LCQ mass spectrum. We aimed to explore the effects of AB on the VMC children by investigating peripheral Treg cell homeostasis. A total of 68 VMC children were random and evenly assigned into an AG group (receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…In our previous study, As-IV exerts cognitive benefits and promotes hippocampal neurogenesis and synaptic plasticity in stroke mice via Wnt pathway. IL-17 expression is downregulated by administering As-IV 29 , which is consistent with the results in other acute diseases [30][31][32] . Therefore, it seems that As IV could be a promising strategy in the therapeutic arsenal against ischemic cortex after stroke for its effect on activating proliferation and promoting neurogenesis.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our previous study, As-IV exerts cognitive benefits and promotes hippocampal neurogenesis and synaptic plasticity in stroke mice via Wnt pathway. IL-17 expression is downregulated by administering As-IV 29 , which is consistent with the results in other acute diseases [30][31][32] . Therefore, it seems that As IV could be a promising strategy in the therapeutic arsenal against ischemic cortex after stroke for its effect on activating proliferation and promoting neurogenesis.…”
Section: Introductionsupporting
confidence: 90%
“…6a). Previous studies have suggested that As-IV inhibits IL-17 expression 30,32 and pro-apoptotic protein Caspase 3 expression 35 in other animal models. In this study, we first observed how As-IV made effect on IL-17 and Caspase 3.…”
Section: Neural Apoptosis In Ischemic Cortex Is Ameliorated By Adminimentioning
confidence: 96%
“…We found that the expression of IL-17 in the ischemic cortex and hippocampus of stroke mice treated with As IV was decreased remarkably by both immunohistochemistry and Western blot analysis (Figures 3A, B) and the expression of IL-17 increased gradually and slowly after stroke as time went on and lagged far behind the appearance of apoptosis ( Figure 3C). Consistently, previous results also suggest that the over expression of IL-17 indicates a poorer treatment effect and prognosis for ischemic stroke (He et al, 2019;Tian et al, 2019;Zhou et al, 2019), which always abolishes some neuroprotective effect (Ma et al, 2018;Sun et al, 2018;Zhao et al, 2019) and it can be reduced by As IV (Jin et al, 2017;Zhang et al, 2018). So, IL-17 expression is upregulated remarkably by ischemic stroke, which can be reversed by As IV, indicating IL-17 is a key regulation factor for As IV's neuroprotective effect on ischemic stroke.…”
Section: A B C Dsupporting
confidence: 78%
“…Some results have suggested that As IV can reduce IL-4, IL-5, and IL-17 levels to inhibit asthmatic effects (Jin et al, 2017) and improve cardiac functions in children with viral myocarditis by reducing the levels of IL-17, IL-21, and caspase-3 (Zhang et al, 2018). We consistently found that the overexpression of IL-17 induced by stroke was downregulated significantly by giving As IV in both the ischemic cortex ( Figure 3A) and ipsilateral hippocampus ( Figure 3B).…”
Section: As IV Reverses the Overexpression Of Il-17 Induced By Strokementioning
confidence: 99%
See 1 more Smart Citation